Optical Properties and Relative Determination of Caffeine in Black Tea Liquor - Monika Rahardjo; Ferry Fredy Karwur; Ferdy Semuel Rondonuwu (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2019)
Caffeine is one of main quality parameter for teas, known for its ability to increase alertness, and has a slightly bitter flavor. As quality parameter, caffeine content will later determine flavor and aroma profile for teas that affect the price in global market. There were many factors that affected chemical compounds in tea, one of it was growth altitude. This research aimed to characterize caffeine spectra from tea liquor using UV-Vis visible which later can be used to relate caffeine content with the altitude of tea sample plantation. The optical transition of caffeine from brewed tea leaves liquor was measured from a variety of black tea products produced according to quality standards for global market. A total of 63 tea samples from four different grades (FANN, PekoFANN, FANN2, and Dust) and from 12 different tea estates in Indonesia have been replicated in their optical transitions and classified on the basis of caffeine content. It was found that caffeine content in tea products may vary depending on the grade and origin of the tea plantation. FANN grade has higher caffeine content that other grades while products from highland tea plantation generally have more caffeine content for all tea grades.